Student Attitude to Future Profession in Field of Information Technology at University Training Stage - Kurbanov, Rashad A. (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of this article is to study such a phenomenon as career growth from the students’ point of view. Today, there is a persistent trend of increasing popularity of professions related to information technology all over the world, and Russian society is no exception in this regard. There is also a transformation that has occurred in the public consciousness, associated with the emergence of new information technologies in our lives and the growth of vacancies for developers and specialists in the field of information technology in General. The purpose of this study is to study the factors that influence the career development of young specialists in the field of information technology in Russian companies. Research methods: as a research method, a questionnaire was used as a method of collecting primary information, which allows to quickly and effectively investigating the attitude of students-future specialists in the field of information technology to the chosen profession. Results of the research: the article considers the concept of a professional career, and examines the students’ attitude to the future profession in the field of information technology. The features of the dynamics of building a career in this field of information technology are revealed. The authors consider the features typical for the sphere of information technologies, as well as identify problem fields, such as acute shortage of personnel; insufficient competence of employees in this sphere; labor migration of personnel; gender bias towards the male sex. It is determined that the concept of a young specialist is being transformed in the field of information technology. This concept has almost no reference to age and mainly characterizes the set of competencies and qualifications that an employee or candidate has in the field of information technology. It is shown that in the career of a specialist in the field of information technology, specialized higher education ceases to play a key role, and the focus shifts mainly towards self- education and self-study. It is revealed that for students-future specialists in the field of information technology, career growth is not only a formal promotion, but also mainly an increase in salary, as well as in the development of their professional skills and competencies. The data obtained in this work can be used in social psychology, labor psychology, Economics, age psychology, as well as for further theoretical development of this issue.